Teo Estetis Canang Sari - Ida Ayu Tary Puspa; Ida Bagus Subrahmaniam Saitya; Gede Agus Siswadi (Purwadita : Jurnal Agama dan Budaya, 2020)
All human beings who are still bound by kama need beauty and have an aesthetic encouragement. The human need for aesthetic pleasure has encouraged them to continue to create objects of aesthetic value that can cause a sense of lango (fun). Canang sari is an upakara symbolic of gratitude and thanks to the God, with all His manifestations. Aesthetically, the canang sari, besides containing religious values, also has aesthetic value from the reringgitan, the form with the composition, as well as the combination of the four floral colors. The aesthetic value contained therein increasingly makes calm, comfort, pleasure so that it further enhances spiritual religious both for those who make, those who see, and who give to Ida Sang Hyang Widhi Wasa. Theo aesthetics of canang sari will imply satyam (truth), sivam (purity), and sundaram (balance). Keywords: theo aesthetics; canang sari